Africa emerges as the hotbed for edtech - François Hume-Ferkatadji (The UNESCO Courier, 2023)
The health crisis linked to the COVID-19 pandemic has accelerated the use of new educational technologies on the continent. While they open up new possibilities, these innovative solutions come up against inequalities in digital access.